THE INFLUENCE OF FINANCIAL CONSTRAINTS AND STOCK PRICE CRASH RISK THROUGH FIRM’S PROFITABILITY ON THE INFRASTRUCTURE, UTILITIES, AND TRANSPORTATION SECTOR LISTED IN IDX BEFORE AND DURING COVID-19 PANDEMIC - Mashuri, Ardelia Callista; Prabowo, Tri Jatmiko Wahyu (Diponegoro Journal of Accounting, 2021)
In 2020, the world economic condition, especially Indonesia was experiencing a decline due to the Covid-19 pandemic. Financially, this condition weakens the ability of several companies to obtain profits. This capability is defined as profitability. The main purpose of this study is to determine the relationship between the firm's profitability through financial constraints and stock price crash risk on the infrastructure, utilities, and transportation sector companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. The control variables used in this study are the Debt Ratio and Total Asset Turnover. The sample selected using purposive sampling method with multiple linear regression analysis technique through the SPSS program. The sample used in this study were 34 companies in the infrastructure, utilities, and transportation sectors listed on the Indonesia Stock Exchange from 2019 to 2020. The independent variable, financial constraints is measured by firm size and stock price crash risk is measured by the negative coefficient of skewness (NCSKEW). Meanwhile, the dependent variable, firm’s profitability is measured by Return On Assets (ROA) ratio. The results of this study indicate that financial constraints significantly influence the firm's profitability. On the other hand, this study finds that stock price crash risk has no significant influence on firm’s profitability which may be due to the company's negative coefficient of skewness (NCSKEW) value on the infrastructure, utilities, and transportation sector before and during the Covid-19 pandemic is still reasonable.